RESPON REMAJA TERHADAP PERINGATAN BAHAYA MEROKOK DALAM BENTUK TEKS DAN GAMBAR PADA KEMASAN ROKOK - Yunita Syahputri Damanik; Fithri Handayani Lubis (Jurnal Penelitian Kesmasy, 2019)
Health warning in the images Pictorial Health Warning on cigarette packs could actually preventincreasing number of victims of novice smokers. Because of the figures packs of smokingcigarettes, smokers beginners will think again about resume the smoking habits. The research goalis to find response to the warning of the dangers of smoking adolescents in the form of text andpictures on cigarette packs. This research method is qualitative research wich descriptiveexploratory design. Selection participant in this study using a snowball sampling technique. Datawere collected by interview. Data analysis is done manually, where the first researcher to make atranscript of the interview obtained from listen to repeated recording and remarks interview flew(filed notes). Results showed that all the informant knows about the contents of a messagewarning of the dangers of smoking on cigarette packs. No teenagers can name correctly and cleartext content and image are printed on cigarette packs. Teens are afraid of the warning bud didnot make teens stop smoking. This can be caused by the delivery of information is not frequentlyand continuously get by teenagers per day according to the needs and purchasing power of theyouth. It can also because by teens fear whens buying cigarette with the packaging and store itwill likely be examined and acknowledged by parents and supervisors orphanage. It is hoped allparties contribute to preventing and addressing smoking behavior in the adolescent. The approachto preventing and addressing smoking approaches such as providing information about thedangers or negative effects of smoking, but touches affectional necessary.